„Teuflische Verführer“ oder „verdammte Häretiker“?: Nikolaus Magni von Jauer (1355–1435) und die Hussiten - Bracha, Krzysztof (Zeitschrift für Religions- und Geistesgeschichte, 2022)
Nicholas Magni of Jawor (de Jawor/Jauer, von Heidelberg) (1355–1435), a Silesian professor of theology, preacher, and diplomat, was one of the most interesting figures of the first generation of scholars from the University of Heidelberg. Of all his output, it is the treatise De superstitionibus that has attracted the greatest attention so far, while his less known anti-Hussite writings have long been only a research postulate. The work of Jiří Petrášek is, therefore, a long-awaited analysis of the insufficiently recognized writing by Nicholas Magni: Contra epistolam perfidiae Hussitarum, which is a response to the Taborite Manifesto from 1430. In his work, Petrášek draws new conclusions: regarding Nicolas Magni’s views on indulgences, the author points to the borrowings from Henry of Langenstein, and he does not share the earlier statement of Franz X. Bantle about the originality of the Heidelbergian theologian’s views on indulgences and their essence confined to the notion of “communication”. Thus, we receive a work that verifies the previous findings on the anti-Hussite views of Nicholas Magni, and which thoroughly introduces us into the less known areas of the 15th century Catholic anti-Hussite polemics.